Brillouin Erbium Ytterbium Fiber Laser - Ting, Lawrence Sii Ying; Lai, Tian Fat; Wadi Harun, Sulaiman (IEEE, 2008)
This paper presents properties and characterizations of the Brillouin Erbium-Ytterbium Doped Fiber Laser (BEYDFL) system. BEYDFL systems have the potential to become multi-channel source in Dense Wavelength Division Multiplexing (DWDM) system. BEYDFL is a unique laser source that can produces multiple channels simultaneously with dense and constant channel spacing of about 0.084nm. This system utilizes the combination of two gain medium which are Brillouin gain and Erbium- Ytterbium gain to produce laser comb through cascading process. In the characterization stage of BEYDFL, laser comb consists of 22 channels with 1.34dB of channel’s power variation operating in 1535nm region was obtained.